Malignant Ascites - Rabindran Chandran; D Sharad Gedam (International Journal of Medical Research and Review, 2016)
Ascitis is common entity in adults. Increased vascular permeability, decerse plasma oncotic pressure & lymphatic obstructions are common causes.